Does antrum size matter in sleeve gastrectomy? A prospective randomized study - Pizza, Francesco; D’Antonio, Dario; Lucido, Francesco Saverio; Gambardella, Claudio; Carbonell Asíns, Juan Antonio; Dell’Isola, Chiara; Tolone, Salvatore (Surgical endoscopy, 2021)
Background Laparoscopic sleeve gastrectomy (LSG) is a safe and effective bariatric procedure in terms of excess weight loss. Nevertheless, controversies still exist on several technical and operative aspects of LSG. The aim of this study is to evaluate variations in anthropometric features in subjects with a LSG gastric resection starting from 2 cm or 6 cm from the pylorus. Secondary aim was the evaluation of differences in morbidity, food tolerance, and GERD incidence studied with upper endoscopy (UE) and GERD Health-Related Quality-of-Life score. Methods Patients were prospectively randomized into 2 groups: Group A (at 2 cm proximally to the pylorus) and Group B (at 6 cm proximally to the pylorus). All patients were followed-up at 3, 6, 12, and 24 months. UE was performed in all patients at 12 or 24 months. Results One hundred and fifty met the inclusion criteria and were enrolled in the study. The anthropometric features (BMI, %EWL, %TWL) resulted statistically different in the first 12 months (24.2 ± 3.4 vs 27.5 ± 4.3, 63.7 ± 14.1 vs 59.6 ± 12.5 and 42.9 ± 7.4 vs 38.2 ± 6.2), in favor of group A. At 24 months the differences disappeared (25.2 ± 4.4 vs 26.2 ± 3.3, 62.8 ± 13.1 vs 61.6 ± 10.5 and 41.9 ± 7.4 vs 40.2 ± 6.2). An increased GERD was found in both groups postoperatively with a higher incidence in group A at 6-month follow-up. Conclusion Performing the LSG with a radical antrectomy could improve weight loss at 12-month follow-up but expose to lower food tolerance and higher transitory GERD. The differences seem to be reduced to a 24-month.